1994
DOI: 10.1007/bf02599136
|View full text |Cite
|
Sign up to set email alerts
|

Quality of published reports of the prognosis of community-acquired pneumonia

Abstract: Despite improvement in overall quality of published articles, systematic errors exist in the design and reporting of studies related to the prognosis of community-acquired pneumonia. The quality assessment tool employed in this study could be used to guide the development of high-quality outcomes research in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 93 publications
0
6
0
Order By: Relevance
“…The study was designed according to guidelines on investigations into the outcome of patients with community-acquired pneumonia, stressing the importance of properly defining the referral patterns, the inception cohort and follow-up of subjects [11].…”
Section: Methodsmentioning
confidence: 99%
“…The study was designed according to guidelines on investigations into the outcome of patients with community-acquired pneumonia, stressing the importance of properly defining the referral patterns, the inception cohort and follow-up of subjects [11].…”
Section: Methodsmentioning
confidence: 99%
“…113 The weighting assigned to methodological items varies considerably between scales, 117 and does not usually take into account the direction of bias. 119 An investigation comparing low-molecular-weight heparin (LMWH) with standard heparin for thromboprophylaxis in general surgery found that trials identifi ed as 'high quality' by some of the 25 scales investigated indicated that LMWH was not superior to standard heparin, whereas trials identifi ed as 'high quality' by other scales led to the opposite conclusion, that LMWH was benefi cial. 117 It is therefore preferable that aspects of quality such as blinding and treatment allocation (and their potential impact on study results) should be considered individually.…”
Section: The Process Of Quality Assessment In Systematic Reviewsmentioning
confidence: 99%
“…cations, natural history of symptom resolution, and expected time to return to usual activities. 10 Few previously published reports of prognosis for CAP have assessed outcomes other than all-cause mortality, 11 and few have studied patients treated in the ambulatory setting. [12][13][14][15][16][17] As part of the Pneumonia Patient Outcomes Research Team (PORT) project, we conducted a mul-…”
Section: Original Investigationmentioning
confidence: 99%